9 A comparison between three quantitative perfusion post processing methods. (28th January 2023) - Sharrack, Noor; Poenar, Ana-Maria; Scannell, Cian; Higgins, David; Broadbent, David; Benovoy, Mitchel; Chiribiri, Amedeo; Greenwood, John; Plein, Sven
Abstract : Several analysis methods for Quantitative Perfusion (QP) CMR have been proposed, some vendor-specific, others generic. Published literature shows differences in the Myocardial Blood Flow (MBF) between these methods. Current limitations include the lack of consensus on optimal acquisition and analysis techniques, which ideally, should yield MBF and myocardial perfusion reserve (MPR) estimates consistent with, and interchangeable across studies and preferably with PET, which remains the gold-standard [1]. There lack of inter-vendor standardisation remains an important hinderance for the implementation of QP CMR into routine clinical practice. We investigated the differences in global stress MBF, global rest MBF and myocardial perfusion reserve (MPR) between three post-processing quantitative perfusion methods using two field strengths. 27 patients referred for stress myocardial perfusion CMR were recruited. Basic demographic data and CMR data was collected. Two scanners (1.5T Ingenia and 3T Achieva-TX were used. Both sequences used dual acquisition protocols and comparable contrast-agent dosing regimens. Data from both field strengths were grouped and then analysed using 3 different QP methods (A [2], B [3] and C [4] to derive global rest MBF, global stress MBF and MPR. The data were tested for normality and then methods were compared with one another using repeated measures one way ANOVA for parametric data, or Friedman's test for non-parametric data, as appropriate. All patients completed studies with good quality. 20 scans were performed on 1.5T and 7 scans were performed on 3T. Mean Ejection fraction was 55 ±11%, mean age was 65 ±10 years with a male: female distribution (22:5). Mean global stress MBF, rest MBF and MPR for method A were 2.38 ± 0.82 [2.06–2.70], 1.35± 0.55 [1.13–1.56] and 1.98± 0.61 [1.73–2.22] for method B were 2.43 ±0.55 [2.21–2.65], 1.28 ±0.59 [ 1.05–1.51] and 2.02 ± 0.60 [1.78–2.26] and for method C were 2.89 ± 0.50 [2.70–3.09], 1.36± 0.49 [1.17–1.56] and 2.25± 0.55 [2.04–2.45] respectively. There was no statistically significant difference in MPR using the three methods (F(2, 52) =2.39, p=0.102) or in rest MBF (X 2 (2) = 0.92, p= 0.63). Statistically significant differences in stress MBF (F (2, 52) =7.36, p=0.002) were seen. Preliminary analysis of QP at two field strengths and between three analysis methods suggests significant differences in stress MBF results between some QP methods. However, MPR may have better reproducibility. Further studies are required between more QP techniques, incorporating multiple vendor QP implementations to determine clinical utility of QP and for international standardisation.